Efficiency of vertical mechanisms of social regulation in the context of values and settings of young generation - Pinchuk, Ihor V.; Derbin, Alexey P. (Journal of the Belarusian State University. Sociology, 2020)
The article is devoted to the analysis of the effectiveness of the use of vertical (hierarchical) connections by the state in terms of social regulation and their correlation with the current worldview and values of young people. In the refraction of the theory of generations, the specifics of information consumption by of millennials and representatives of generation of Z are described. Based on the analysis of various studies, it is concluded that today new opportunities are forming for individuals in a situation of searching for information and choosing a behavior strategy, the role of horizontal connections is growing. A hypothesis is put forward about the need to expand dispositional principles in social regulation, as well as the implementation of a more flexible approach to the legal regulation of digital information space.
Keywords: youth; the generation of Z; millennials; digitalization; information space; vertical (hierarchical) connections; social regulation